Science Teacher Candidates’ Views on Digital Game Addiction (International Journal of Education in Mathematics, Science and Technology, 2025)
This research was carried out to determine the opinions of science teacher candidates about digital game addiction. For this reason, the phenomenology method which one of the qualitative research methods, was used. The sample of this study consists of 5 science teacher candidates studying at different universities in the 2022-2023 academic year. Criterion sampling method was used when determining the participants. A semi-structured interview form develop by the researcher was used as a data collection tool in the study. The data obtained from the interview form was analyzed using the content analysis method. Through the interviews, it was concluded that the participants saw digital game addiction as constantly playing games, escaping from daily life and moving to the next level. In addition, it has been determined that individuals with digital game addiction display angry and antisocial characteristics. For this reason, it has been suggested to develop games that will make individuals less angry and socialize, and to conduct studies on the effectiveness of these games.
Keywords: Digital game; Digital game addiction; Phenomenology